A self-sensing HTPB liner for non-destructive monitoring nitroglycerin (NG) migration at the interface between double base propellant and the HTPB liner - Jie Wang; Bo Liu; Yanchun Li; Mengqi Chen; Qian Guo; Dongming Song; Aifeng Jiang (Defence Technology)
During the storage of composite propellants, the migration of plasticizers and other unbonded additives at the interfaces of liner adhesives has garnered significant attention in understanding liner failure mechanisms, aging processes, and safety performance. However, there is currently no non-destructive and quantitative detection method for migration of plasticizers in propellant liner. In this study, we developed a HTPB sensing liner by incorporating conductive fillers—namely carbon black (CB), carbon nanotubes (CNTs), and graphene nanoplatelets (GNP)—into the HTPB matrix. The synergistic interaction between CNTs and GNP facilitates the formation of a tunneling conductive network that imparts electrical conductivity to the HTPB liner. To elucidate the functional relationship between conductivity and nitroglycerin (NG) migration, we applied the HTPB sensing liner onto double base propellant surfaces and measured both the conductivity of the sensing layer and NG migration during a 71 °C accelerated aging experiment. The results shows that when CNTs/GNP content reaches 3wt%, there is an exponential correlation between conductivity and NG migration with a fitting degree of 0.9652; the average response sensitivity of ΔR/R0 relative to NG migration is calculated as 41.69, with an average deviation of merely 5.67% between NG migrations derived from conductivity fittings compared to those obtained via TGA testing results. Overall, this sensing liner exhibits excellent capabilities for detecting NG migration non-destructively and quantitatively while offering a novel approach for assessing interfacial component migrations as well as debonding defects in propellants—a promising avenue for future self-monitoring strategies regarding propellant integrity.